Feasibility of Learning Devices with Guided Inquiry Model to Develop Senior High School Students’ Science Process Skills - Nurhuwaida Nurhuwaida; Mastuang Mastuang; Misbah Misbah; Mohd Ali Ibrahim (JPPS (Jurnal Penelitian Pendidikan Sains), 2022)
This research aims to produce learning devices with guided inquiry models that are valid, practical, and effective, making them worth using to practice students' science process skills. This development research uses the ADDIE model. Developed the device in a trial to grade XI students at one of the State High Schools in Banjarmasin. Data collection uses learning device validation sheet instruments, lesson plan implementation, observation sheets, and learning outcome tests. The results showed that the learning tools developed: (1) valid based on the assessments of academics and practitioners, (2) practical based on the implementation of the lesson plan, and (3) effective with medium categories based on N-gain results of learning outcomes. Concluded that learning devices with guided inquiry models deserve to be used to practice students' science process skills. This learning device can be one of the alternatives, especially in temperature and heat materials at the High School level.